2020
DOI: 10.1021/acs.estlett.0c00875
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Monitoring of SARS-CoV-2 RNA on High-Touch Surfaces in a Community Setting

Abstract: Environmental surveillance of surface contamination is an unexplored tool for understanding transmission of SARS-CoV-2 in community settings. We conducted longitudinal swab sampling of high-touch non-porous surfaces in a Massachusetts town during a COVID-19 outbreak from April to June 2020. Twenty-nine of 348 (8.3%) surface samples were positive for SARS-CoV-2 RNA, including crosswalk buttons, trash can handles, and door handles of essential business entrances (grocery store, liquor store, bank, and gas statio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
124
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(150 citation statements)
references
References 73 publications
8
124
3
Order By: Relevance
“…For example, the canines in this study detected and alerted to items such as garbage bins, office desks, folders/files, chairs and air filters in filtration units. A recent study by Harvey et al reported 8.3% of surfaces swabbed and sampled, including garbage can lids, crosswalk buttons, and door handles, were positive for SARS CoV-2 RNA [ 51 ]. While this is an ongoing study, these four canines do support other studies that have conducted COVID-19 environmental surveillances.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the canines in this study detected and alerted to items such as garbage bins, office desks, folders/files, chairs and air filters in filtration units. A recent study by Harvey et al reported 8.3% of surfaces swabbed and sampled, including garbage can lids, crosswalk buttons, and door handles, were positive for SARS CoV-2 RNA [ 51 ]. While this is an ongoing study, these four canines do support other studies that have conducted COVID-19 environmental surveillances.…”
Section: Discussionmentioning
confidence: 99%
“…The literature contains reports showing detection of SARS-CoV-2 in hospital environments 12,13,19 . However, it has been recently reported that the risk of acquiring COVID-19 by touching contaminated surfaces in less than 5 in 10,000 20 . In addition, although SARS-CoV-2 RNA has been detected in hospital environment the virus could not be isolated in cell culture 19 .…”
Section: Discussionmentioning
confidence: 99%
“…RNA from SARS-CoV-2 has been found on surfaces in hospitals [ [27∗] , [28∗] , [29] , [30] , [31] , [32] ], laboratories [ 33 ], and public places [ 32 , 34 ]. Here we summarize some of the results of sampling for viral RNA by the polymerase chain reaction technique (PCR).…”
Section: Sars-cov-2 Rna On Public Surfacesmentioning
confidence: 99%
“…Harvey et al [ 34 ] explored the presence of virus in public places over 2 months (from April to June 2020). They checked door handles, gas pump handles, ATM keypads, garbage cans, crosswalk buttons in essential businesses (i.e., grocery stores, banks, gas stations, restaurants, laundromats, and a few more).…”
Section: Sars-cov-2 Rna On Public Surfacesmentioning
confidence: 99%